2020
DOI: 10.3390/vaccines8030527
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Differences in the Preference for Hepatitis B Virus Vaccination: A Discrete Choice Experiment

Abstract: Understanding behavioral factors differences in the preferences for vaccinations can improve predictions of vaccine uptake rates and identify effective policy interventions to increase the demand for vaccinations. In this study, 353 adults in Shandong province in China were interviewed about their preferences for hepatitis B virus (HBV) vaccination. A discrete choice experiment (DCE) was employed to analyze the preference for HBV vaccinations, and a mixed logit model was used to estimate respondent preferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…Risk aversion did not significantly affect our multiple regression models, and it decreased the model's performance when entered the ML model. In this manenr, we cannot provide further insights into the debate on whether risk aversion has a positive or negative role in vaccine hesitancy [42,43].…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…Risk aversion did not significantly affect our multiple regression models, and it decreased the model's performance when entered the ML model. In this manenr, we cannot provide further insights into the debate on whether risk aversion has a positive or negative role in vaccine hesitancy [42,43].…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…Behavioural studies on other vaccines have shown that the decision to vaccinate is often based on factors that are the focus on the Health Belief Model (HBM)-such as perceived benefits, perceived effectiveness of the vaccine (also known as perceived action efficacy), perceived vaccine side-effects, and reduced perceived risk of infection by COVID-19 [19]. Systematic reviews on behavioural determinants have shown that assessing determinants that are included in the HBM revealed significant determinants associated with the acceptance of human papillomavirus [20] and influenza-vaccination uptake [21].…”
Section: Introductionmentioning
confidence: 99%
“…The use of economic models when studying vaccine acceptance or hesitancy exhibit some shortcomings in describing the determinants [ 23 , 29 , 30 ]. Behavioral studies have shown that the decision to vaccinate is often based on perceived benefits, effectiveness, and perceived risk of vaccine side-effects versus infection [ 31 ]. Systematic reviews on behavioral determinants of health have shown that the HBM was useful in identifying determinants associated with the acceptance of Human Papillomavirus (HPV) [ 29 ] and influenza vaccination uptake [ 32 ].…”
Section: Introductionmentioning
confidence: 99%